2016
DOI: 10.1111/jon.12372
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord MR Diffusion Properties in Patients with Degenerative Cervical Cord Compression

Abstract: Diffusion parameters of the cervical spinal cord were thus shown to respond significantly to spinal cord compression, but were subject to interaction with several other factors including sex, age, and SCL. These findings may be important to the interpretation of DTI measurements in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
3
25
1
1
Order By: Relevance
“…Recently, a larger study was completed with 92 ASCC and 71 uncompressed subjects, but DTI differences between these groups were not reported. 22 Our finding that rostral CSA was significantly greater among ASCC subjects suggests that atrophy does not occur in this condition, but rather, having a larger spinal cord appears to be a predisposing factor for compression, in keeping with a prior report that investigated spinal canal occupation ratio. 7 MCL CSA was also (non-significantly) larger in uncompressed subjects, but the ratio of MCL to rostral CSA showed a trend towards being decreased in ASCC, indicating that the mild compression observed in ASCC subjects has only a minor effect on CSA, and normalisation by rostral values helps to mitigate the high intersubject variability of this measure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, a larger study was completed with 92 ASCC and 71 uncompressed subjects, but DTI differences between these groups were not reported. 22 Our finding that rostral CSA was significantly greater among ASCC subjects suggests that atrophy does not occur in this condition, but rather, having a larger spinal cord appears to be a predisposing factor for compression, in keeping with a prior report that investigated spinal canal occupation ratio. 7 MCL CSA was also (non-significantly) larger in uncompressed subjects, but the ratio of MCL to rostral CSA showed a trend towards being decreased in ASCC, indicating that the mild compression observed in ASCC subjects has only a minor effect on CSA, and normalisation by rostral values helps to mitigate the high intersubject variability of this measure.…”
Section: Discussionsupporting
confidence: 89%
“… 7 14 Although the groups with and without cord compression differed significantly in age and weight, all MRI metrics were corrected for age and none showed significant variation with weight. In fact, MTR and FA have previously been shown to vary with age, 11 14 but these relationships became non-significant when compression was included in the analysis, confirming a recent DTI study, 22 and suggesting that earlier studies may have overestimated the effect of age. 14 23 24 Spinal cord compression was primarily anterior in all subjects, and this appeared to preferentially cause injury to the ventral columns, as measured by reduced FA and MTR.…”
Section: Discussionsupporting
confidence: 59%
“…Although significant relationship between age and dMRI metrics was previously observed in a healthy aging population 37 or in patients with degenerative cervical cord compression 16 , none of the models identified age variable as the model-significant variable in the present data, suggesting that the age-effect in the dataset is low.…”
Section: Resultscontrasting
confidence: 79%
“…We showed that the proposed protocol was able to distinguish age-comparable healthy controls and presymptomatic patients with microstructural myelopathy. Changes in dMRI parameters for DCM patients with advanced clinical symptoms have been already reported [12][13][14][15][16][17][18] . Extending the dataset with groups of symptomatic DCM patients spanning from mild to severe cervical SC compressions to delineate the disease progression in all DCM stages will be addressed in upcoming research.…”
Section: Hardi-zoomit Protocol and Data Analysis Innovations Our Promentioning
confidence: 61%
“…Interessanterweise fand sich eine eindeutige Korrelation der DTI-Parameter mit dem Alter, nicht aber mit dem Geschlecht. Kerkovsky und Kollegen [16] kamen in einer großen prospektiven Studie, die eine Kohorte von 71 gesunden Individuen beinhaltete, teilweise zu anderen Ergebnissen: Hier zeigten sich zwischen den unterschiedlichen HWS-Segmenten signifikante Unterschiede bei den DTI-Parametern und das Geschlecht hatte einen signifikanten Einfluss auf die ADC-Werte. Die Ergebnisse dieser beiden Studien zeigen repräsentativ, dass DTI-Parameter schon bei gesunden Probanden abhängig von unterschiedlichen Einflussfaktoren variieren können.…”
Section: Dti-parameter Bei Gesunden Probanden Und Myelopathie-patientenunclassified